2020
DOI: 10.1063/5.0011299
|View full text |Cite
|
Sign up to set email alerts
|

Influence of glow discharge on evolution of disturbance in a hypersonic boundary layer: The effect of second mode

Abstract: This is the companion volume on the effects of artificial disturbance on the transition process of a boundary layer over a flat plate. The artificial disturbance with the frequency in the range of second-mode instability is introduced into the boundary layer by glowing discharge on the surface of the plate. Experiments are performed using Rayleigh-scattering visualization, wall pressure pulsations measurement, and high-frequency schlieren visualization in the Φ300 mm hypersonic quiet wind tunnel at Peking Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…This result is consistent with experimental results in the flat boundary layer (Zhang et al. 2020), wherein the low-frequency waves are observed to transfer energy to the second mode wave via a similar phase difference locking mechanism. There is no phase difference locking mechanism between the cross-flow instability and the first mode nor between the second mode and the first mode.…”
Section: Analysis and Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This result is consistent with experimental results in the flat boundary layer (Zhang et al. 2020), wherein the low-frequency waves are observed to transfer energy to the second mode wave via a similar phase difference locking mechanism. There is no phase difference locking mechanism between the cross-flow instability and the first mode nor between the second mode and the first mode.…”
Section: Analysis and Discussionsupporting
confidence: 92%
“…Later, Li et al. (2020) and Zhang, Li & Lee (2020) extended the phase-locked mechanism to the interaction of different frequency disturbances, holding that the phase velocity locking mechanism can explain the interaction between the second mode and the first mode, and the second mode can transfer energy to the first mode through the phase velocity locking mechanism. In addition, the phase difference locking mechanism can explain the interaction between the first mode and the second mode, which causes the first mode to transfer energy to the second mode.…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2020, Li et al introduced high-frequency glow discharge (105 kHz) as an artificial disturbance in a hypersonic flat boundary layer. The simulation results indicated that glow discharge plasma disturbance has significant effects on the second-mode unstable wave and can effectively trigger boundary layer transition [28]. The purpose of the introduction of high-frequency artificial disturbance is to experimentally explore the nonlinear mechanism of second-mode and the first-mode waves in the transition process of the hypersonic plate boundary layer.…”
Section: Introductionmentioning
confidence: 99%